Empowering Higher Education Extension Workers for Community Engagement: The Case of a Certificate Course Offered by a Comprehensive University in Manila - Abenir, Mark Anthony Dayot (Archīum Ateneo, 2020)
Even though community engagement is an important function of higher educational institutions (HEIs), many HEI personnel across the world are in need of training in this area. In the extant literature, trainings for community engagement in an HEI context are well studied in countries of the Global North. However, there seems to be a dearth of literature about this field in the Philippines. Our research addresses this gap by delving into the certificate course on community engagement and organizing offered by the University of Santo Tomas (UST) in Manila. Specifically, this study describes the content and conduct of the course, presents the satisfaction evaluation results of course participants, and examines their learnings and insights. This study contributes to the literature by documenting efforts made by HEIs in the Philippines in mainstreaming community engagement in the fabric of academic life.